Wondrous geographies and historicity for state-building on Malaita, Solomon Islands - Bond, Nathan (Journal of religious and political practice, 2017)
Contemporary anthropological debates over the political implications of the global explosion of Evangelical and Pentecostal forms of Christianity frequently center on a 'break with the past' and reliance on the working of divine power. In this article, we intervene in this debate by exploring people's wonder about new global geography and historicity and the ways in which this wonder is opening up a space for local state building by an Evangelical/Pentecostal movement on the island of Malaita, Solomon Islands. We present and discuss the origins of a particular theocratic impulse of this movement to show how the movement's theology evokes and supports the institution of a form of governance. This challenges the widespread observation that Evangelical/Pentecostal believers are politically quiet.